'The Citadel of Scholarship': Rediscovering Critical IR in Millennium 1:1. (October 2022) - Conway, Philip R.
'Critical' international relations (IR) is usually understood to have originated in the early 1980s. However, a close reading of Vithal Rajan's 'An Epitaph for Detached Scholarship', published in the inaugural issue of Millennium in 1971, tells another story. Rajan's article was not a work of critical theory per se, but it was in tune with demands, at this time, for establishing a 'critical university'. Promising to open up university education to all, dispensing with traditional curricula and authoritarian modes of teaching, the critical university, like Rajan's article, has long since been forgotten. Nevertheless, this moment set the scene for the professionalised establishment of 'critical' academia in the decades to come. Rediscovering Rajan's 'Epitaph' thus offers to reconnect critical IR with an earlier, and perhaps more generative, moment of inception. Indeed, even today, Rajan's creative, provocative, playful text stands out as a rewardingly undisciplined contribution to the discipline.